COMPREHENSIVE DIAGNOSIS OF HYPOGONADOTROPIC HYPOGONADISM IN NONFUNCTIONING PITUITARY ADENOMAS: A CLINICAL AND INSTRUMENTAL PERSPECTIVE (International Educators Conference, 2025)
Hypogonadotropic hypogonadism (HH) is a common clinical manifestation of pituitary insufficiency, particularly in tumors of the chiasmatic-sellar region. Timely diagnosis plays a crucial role in preventing complications associated with hormonal imbalances and reproductive dysfunction.